Teaching Reading Comprehension Using Highlighting Underlining Glossing Strategy - Hamid Ismail; Saiful; Rina Asrini Bakri; Sumirna (Jurnal Pendidikan dan Pembelajaran, 2022)
The aim of this research project is to learn more about students' reading comprehension through the application of H.U.G. penultimate. Utilizing a single pre-experimental method with desired results pre-test, post-test. A baseline test was administered to each participant, followed by a treatment plan consisting of eight therapy sessions, and finally a final test. The subject of this essay is the second grade, students of SMAN 13 Gowa, for the 2019/2020 school year. From here. Ten. Classes consist of orderly and orderly classes for each student. The class consists of 35 women. In this case, the total population is 0.350 students. Due to the heterogeneity of students in learning English, the researchers used a purposive sampling technique. Researchers, however, chose a different class to serve as their personal watchman. As a result, the total number of participants in this study is 35. The mean score for the participants in the pre-test was 54.85, while the post-test score for the participants was.81.82. Then there was a average correction, with the post-test student score being higher than the pre-test score. Development of students' reading skills. understanding is proven by value. the. pre-test, which is higher than the value of t-table. (17,320>3,081). This indicates that students in Grades II and SMA 13 Gowa can comprehend written material specifically by using the strategies of Highlighting, Underlining, and Glossing. Students' understanding and their talent for reading texts. Afterward, the researcher concluded that the use of Highlighting Underlining and Glossing strategies in reading material could improve the class is composed of 35 students.